Short-Term Isoflavone Intervention in the Treatment of Severe Vasomotor Symptoms after Surgical Menopause: A Case Report and Literature Review - Supanimit Teekachunhatean; Natnita Mattawanon; Surapan Khunamornpong (Hindawi Limited, 2015)
Isoflavones are soy phytoestrogens that potentially exert various favorable effects in postmenopausal women, for example, alleviating vasomotor episodes, attenuating bone loss, and stimulating vaginal epithelial maturation. There has, however, been lack of consensus regarding those therapeutic effects. Most clinical studies of isoflavones have been conducted with women who had undergone natural menopause, but not those who had undergone surgical menopause. This study reports on a 51-year-old woman who presented with severe vasomotor episodes after undergoing a hysterectomy and a bilateral oophorectomy due to hypermenorrhea secondary to myoma uteri. She refused hormone therapy due to fear of adverse drug reactions so was treated with oral soy isoflavones (two capsules twice daily, equivalent to at least 100 mg daily dose) for 8 weeks. The number and severity of hot flushes and her menopause-specific quality of life dramatically improved from baseline values. The serum bone resorption marker (beta C-telopeptide) decreased markedly, while vaginal epithelial maturation improved slightly, suggesting the potential of isoflavones in attenuating bone loss and stimulating vaginal maturation. The intervention did not adversely affect the hormonal profile (FSH, LH, and estradiol) and liver or renal functions. Thus, isoflavones could be an option for women experiencing severe vasomotor episodes after surgical menopause.